Agile Project Management: STEERING FROM THE EDGES. - Augustine, Sanjiv; Payne, Bob; Sencindiver, Fred; Woodcock, Susan (Communications of the ACM, 2005)
This article discusses the dangers of a volatile organizational environment that challenges persons managing software development projects and suggests ways to avoid them. Agility in project management allows managers and employees to adapt to changing circumstances, instead of apply rigid, formal development methods. The authors describe the use and make-up of complex adaptive systems as a tool for agile management. INSET: COMPLEX ADAPTIVE SYSTEMS.